A Discrete Emotions Perspective to Negative Autobiographical Recall among Younger and Older Adults. Issue 5 (20th October 2019) - Allard, Eric S.; Hamilton, Lucas J.
ABSTRACT: Background : The discrete emotions approach predicts differential relevance of anger and sadness experiences to well-being between younger and older adults (anger more relevant in young adulthood, sadness more relevant in old age). Methods : We tested these assumptions within a semi-guided autobiographical recall task among a sample of younger and older adults. Participants recalled a series of 50 negative past life events that were categorized as to the primary emotion elicited. Phenomenological ratings included assessments of event negativity, positivity, vividness, and age at which the event occurred. Results : Contrary to expectations, there were no age differences in the ratio of anger and sadness experiences, as well as perceived negativity and vividness. However, perceived positivity of sadness events was higher among older relative to younger adults. Conclusion : We discuss the present results in terms of how various emotional events maintain their representational nature in old age, while certain events could be particularly unique to divergent age-related well-being outcomes.